Advertising age: the principles of advertising of work - Thorson, Esther (Illinois: NTC. Business Books, 1989)
Advertising agencies and their clients.- Legal concerves in advertising.- Social critique and concerve with advertising.- Advertising research, product, positioning and market segmentation, media, creative estrategies and executions, advertising is support system, packging, promotions and direct mk, global advertising, advertising education and the job market.
Incluye bibliografía
Keywords: Publicidad